2018
DOI: 10.1177/0956797618764621
|View full text |Cite
|
Sign up to set email alerts
|

Mind-Body Practices and the Self: Yoga and Meditation Do Not Quiet the Ego but Instead Boost Self-Enhancement

Abstract: Mind-body practices enjoy immense public and scientific interest. Yoga and meditation are highly popular. Purportedly, they foster well-being by curtailing self-enhancement bias. However, this "ego-quieting" effect contradicts an apparent psychological universal, the self-centrality principle. According to this principle, practicing any skill renders that skill self-central, and self-centrality breeds self-enhancement bias. We examined those opposing predictions in the first tests of mind-body practices' self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 38 publications
4
65
1
1
Order By: Relevance
“…Importantly, however, we found that agentic SE was linked not only to a more agentic reputation but also to a less communal reputation and hence to not getting along with others particularly well. The negative relation between agentic SE and informant-reported communion might explain why SE is perceived as problematic across all world religions (Gebauer, Nehrlich et al, 2017; Gebauer, Sedikides, et al, 2017). A major reason for religiosity’s success is that religiosity binds people in communal in-groups (Graham & Haidt, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, however, we found that agentic SE was linked not only to a more agentic reputation but also to a less communal reputation and hence to not getting along with others particularly well. The negative relation between agentic SE and informant-reported communion might explain why SE is perceived as problematic across all world religions (Gebauer, Nehrlich et al, 2017; Gebauer, Sedikides, et al, 2017). A major reason for religiosity’s success is that religiosity binds people in communal in-groups (Graham & Haidt, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The first concerns the prevalence of agency and communion in the self‐concept. People prefer agency in themselves (Abele & Wojciszke, ) but describe themselves as primarily communal (Abele et al, ; Nehrlich, Gebauer, Sedikides, & Schoel, ; Wojciszke, Baryla, Parzuchowski, Szymkow, & Abele, ). This acknowledged contradiction (Abele & Wojciszke, ) vanishes when considering the division of the self into individual, relational, and collective.…”
Section: Discussionmentioning
confidence: 99%
“…An important asset of jointly studying agentic and communal narcissism is that we were able to account for communal narcissism in our analyses of agentic narcissism (and vice versa). That way, we were able to assure that our agentic narcissism results are not spurious due to communal narcissism (and vice versa) (Gebauer, Nehrlich, et al, 2018; Gebauer et al, 2012). For the same approach regarding two other narcissism dimensions, see Back et al (2013) and Leckelt et al (2015).…”
Section: Overview Of the Present Researchmentioning
confidence: 95%
“…In all, grandiose narcissism comprises agentic and communal forms. To study grandiose narcissism most comprehensively, it is, thus, vital to assess both forms (Gebauer, Nehrlich, et al, 2018; Gebauer, Sedikides, & Schrade, 2017). We do so in the present research.…”
Section: Agentic and Communal Narcissismmentioning
confidence: 99%